PRODUCING CALCIUM-PHOSPHATE COATINGS ON TI-Al-V ALLOY FOR RECONSTRUCTIVE SURGERY APPLICATION - KALINICHENKO, OLEH; KOVALOV, STANISLAV; SUKHYI, KOSTIANTYN; YEFANOV, VOLODYMYR; SUKHYI, MYKHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Due to the extensive aggression by the Russian Federation and the invasion of Ukraine’s territory, more than 100,000 military men and civilians have suffered serious injuries. This has created an urgent need for further development and improvement of the surface treatment technologies of medical implants. This article discusses the necessity of this enhancement to improve the quality of medical care and meet the medical needs of Ukrainian citizens. The need for improvement in implants and medical rehabilitation tools of domestic production places a task before Ukrainian scientists and experts to develop new technologies that meet modern standards of quality and effectiveness. The work is dedicated to the synthesis and investigation of the properties of calcium-phosphate coatings on the titanium alloy Ti-6Al-4V, obtained by the method of anodic-spark oxidation in aqueous solutions of Ca and P salts. The broad capabilities of this method allow for the production of oxide-ceramic coatings with high adhesion to the substrate, predictable composition, adjustable thickness and porosity, making them suitable for medical application (reconstructive, maxillofacial surgery, implantology). This is a key aspect of meeting the medical needs of our country in times of emergencies and ensuring the nation’s health. The results obtained by the authors demonstrate that with the correctly selected solution and deposition regime, it is possible to obtain even porous coatings containing Ca and P compounds. The proposed coatings have lower microhardness than the alloy, this has a positive impact on the human body as it reduces the modulus of elasticity and, consequently, the stress on the body and the risk of rejection. The thickness, porosity, roughness, and chemical composition of the coating can be regulated by changing the electrolyte concentration and deposition modes, which is an additional advantage of the technology as a whole. However, research and improvement of implantation materials are of utmost importance because the quality of these materials directly impacts people’s lives and health. Therefore, the coatings obtained are subject to further testing and refinement.